Psychological Conditions of the Development of Cognitive Activity in Preschool Age - Samkova I.A (Moscow State University of Psychology and Education, 2019)
The article presents the results of an experimental study of the psychological conditions of the development of cognitive activity in preschool age. The study sample included 89 children from 3 to 7 years old. The hypothesis that the development of cognitive activity is interconnected with the development of visual-figurative thinking and imagination is experimentally confirmed. To identify the age specificity of the relationship between the development of cognitive activity and the development of cognitive abilities, a comparison of the results of the study was carried out using factor analysis separately in each age group. On the basis of this, the psychological conditions for the development of the cognitive activity of preschoolers are defined - this is the development of sign-symbolic mediation and the formation of an inter plan of action. The identified psychological conditions make certain adjustments in the identification of priorities in the educational content for preschoolers, and open up opportunities for creating new educational strategies that will enrich and harmonize the child's cognitive and emotional development.